2015
DOI: 10.1136/bcr-2014-207541
|View full text |Cite
|
Sign up to set email alerts
|

Aceruloplasminaemia: a rare but important cause of iron overload

Abstract: SUMMARYWe present a case of a 20-year-old man referred to our service with iron overload and mildly deranged liver biochemistry. Although liver histopathology was consistent with haemochromatosis, iron studies were not consistent with this diagnosis. Serum ceruloplasmin levels were undetectable, leading to a diagnosis of aceruloplasminaemia. Unlike other iron overload disorders, neurological complications are a unique feature of this illness, and often irreversible, once established. The patient was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
(12 reference statements)
2
14
0
Order By: Relevance
“…When the patient is without significant neurological symptomatology, ideally when they are asymptomatic, an early start to chelatase treatment is considered to be a basic factor for its success [17,26]. In accordance with the literature data, we recorded a reduction in the concentration of serum ferritin.…”
Section: Discussionsupporting
confidence: 80%
“…When the patient is without significant neurological symptomatology, ideally when they are asymptomatic, an early start to chelatase treatment is considered to be a basic factor for its success [17,26]. In accordance with the literature data, we recorded a reduction in the concentration of serum ferritin.…”
Section: Discussionsupporting
confidence: 80%
“…This estimation has obvious regional limitations, and cannot be applied in non-Japanese population, where ACP prevalence is actually unknown. Few more than one hundred of patients have been described in the literature so far, with a worldwide geographical distribution (Miyajima and Hosoi, 1993–2018; Kono, 2013; Doyle et al, 2015; Vroegindeweij et al, 2015; Pelucchi et al, 2018; Riboldi et al, 2018; Yamamura et al, 2018). While Japanese patients with neurological involvement still represent the majority (Miyajima and Hosoi, 1993–2018) the second group is represented by Italian patients reported by some referral centers for disorders of iron metabolism (Pelucchi et al, 2018).…”
Section: Epidemiologymentioning
confidence: 99%
“…This early identification of aceruloplasminemia subjects enabled the exploration of effect of chelation therapy in the pre-neuro-symptomatic phase. Importantly, studies reported that these still asymptomatic individuals remained free of neurologic symptoms during follow-up lasting up to 10 years [44,46,58,59,[61][62][63][64]. Lifelong iron chelation therapy may thus potentially prevent neurologic symptoms.…”
Section: Aceruloplasminemiamentioning
confidence: 99%